Eficacia del celecoxib en el manejo de nocturia secundaria a hiperplasia benigna de próstata en pacientes que vienen recibiendo tamsulosina atendidos en el hospital Belén de Trujillo - Castillo Valle, Juan Javier (2014)
To determine whether treatment with Celecoxib is effective in the management of nocturia secondary to benign prostatic hyperplasia. Material and Methods : A prospective , comparative, longitudinal , observational study . The study population was they comprised 54 patients with IPSS ≥ 8 secondary to benign prostatic hyperplasia have been receiving tamsulosin treated in outpatient clinics of Hospital Belen de Trujillo between December 1, 2012 and May 31, 2013 . Were divided into two groups , Group 1 (27 patients) Tamsulosin 0.4mg daily and Group 2 (27patients ) Tamsulosin 0.4mg + Celecoxib 100 mg. Control symptoms was conducted per month. Results: In the group treated only with Tamsulosin ,nocturia improved in 20 patients (74.07 %). The Tamsulosin + Celecoxib treated group also showed improvement , improving nocturia in 27 patients (100 %). Statistically significant difference in improvement of symptoms in patients treated with tamsulosin or tamsulosin + Celecoxib (P <0.05) Conclusion : Use of Tamsulosin + Celecoxib is effective in the management of nocturia secondary to benign prostatic hyperplasia